A new endemic species of Polystachya (Polystachyinae) from eastern Tanzania - Cribb, Phillip James 1946-
Polystachya nguruensis, a new endemic species from the isolated Nguru Mountains of eastern Tanzania, is described here, and its affinities and conservation status are discussed. Polystachya nguruensisdiffers from P. lukwangulensis in having much longer, more obviously several-noded pseudobulbs, shorter, narrowly oblong-elliptic, coriaceous leaves, and a longer, more densely many-flowered, branching inflorescence with smaller flowers and ecallose lip with a narrowly oblong a midlobe with a broadly obovate to subcircular, apiculate, lip midlobe. Unlike most allied species, it is a lithophyte, growing on sloping slabs of crystalline rock, a highly vulnerable habitat that has already been partly destroyed by fire. Consequently, it is assessed to be Critically Endangered and in need of immediate conservation attention.